Nutrition Education and Local Food Processing Training as a Strategy to Address Undernutrition among Children under Five - Indrastata, Naja Naura Noor; Wardahana, Desfriana Fatika; Auliasari, Sabrina Nabila; Musfirotin, Alfina Uli; Khoiriyah, Romyun Alvy; Mustika, Ika (International Conference on Sustainable Health Promotion, 2025)
Undernutrition among children under five remains a major public health challenge requiring continuous intervention. This study aimed to improve the knowledge and skills of posyandu cadres through nutrition education and demonstrations of local food processing in the working area of Medokan Ayu Public Health Center, Surabaya. An observational study with a cross-sectional design was employed, and samples were selected using cluster random sampling. Primary data were obtained from pre-tests, post-tests, and observations of cadre participation, while secondary data included the health center profile, socioeconomic conditions, and child nutrition data. The intervention consisted of nutrition education and demonstrations of local supplementary feeding (PMT) in the form of moringa leaf and turmeric dim sum. The results showed a significant increase in cadre knowledge, with mean pre-test scores rising from 80.33 to 88.00 in the post-test (a difference of 7.67 points). The Wilcoxon test produced a p-value of 0.001 (<0.05), indicating a statistically significant improvement. A total of 53.3% of respondents experienced increased knowledge, 40% remained unchanged, and 6.7% decreased. These findings demonstrate that nutrition education combined with local PMT cooking demonstrations is effective in enhancing the knowledge and skills of posyandu cadres as community change agents to reduce theprevalence of undernutrition amongchildren under five.